Dataset of computed N-value and factual N-value traced for Soil Subsurface Profiling - Jusoh H.; Sabariah binti Abd Manan T.; Beddu S.; Osman S.B.S.; Jusoh M.N.H.; Mohtar W.H.M.W.; Khan T.; Kamal N.L.M.; Ghanim A.A.; Ismail M.; Abdullah M.T. (Elsevier Inc., 2023)
Soil requires load bearing impact assessment for stability. Therefore, this study aims to utilize the multi-channel analysis surface wave (MASW) for soil subsurface investigation and profiling around Peninsular Malaysia. The standard penetration test (SPT) was conducted for comparison between factual N-value and computed N-value from shear wave velocity (Vs) obtained from MASW using the Imai and Tonouchi equation. The correlation coefficient (R) and coefficient of determination, (R2), showed strong relationship between factual N-value and computed N-value. The model of Vs and factual N-value data distribution is non-normal but the analyzed relationship shows a significant level of p-value < 0.05. The R2 for each location of Vs-N-value relationship are ranging from 0.5 to 0.9. 2020 The Author(s)